Improving Text Reading Comprehension Using Picture Story Media in Indonesian Language Learning for Elementary School Students - Karim Karim; Muhammad Yusnan; Farisatma Farisatma; Krisnawati Krisnawati; Kamasiah Kamasiah (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
This research aims to improve reading comprehension of texts using picture story media. This type of research is classroom action research, using the Kemmis and Mc Taggart model. This research consisted of four steps, namely, planning, action, observation and reflection, and was carried out in two cycles. The data collection technique used in this research is through tests, observation and documentation. This is proven by research data, namely the results of the pre-cycle test, there were 6 students who completed or 42.85% of all students who got ≥ 65, in the first cycle there were 15 students who finished or 71.47 of all students who got a score ≥ 65, while the results of the second cycle test were 19 students who completed it or 90.47% of all students who got a score ≥ 65. The results of this study show that using picture story media can increase understanding of reading texts from cycle I to cycle II by 90 .47%.